Study on Metabolic Trajectory of Liver Aging and the Effect of Fufang Zhenzhu Tiaozhi on Aging Mice - Luo, Duosheng; Li, Jingbiao; Chen, Kechun; Yin, Yifan; Fang, Zhaoyan; Pang, Huiting; Rong, Xianglu; Guo, Jiao (Frontiers in Pharmacology, 2019)
The aim of this study was to investigate the metabolic trajectory of liver aging, the effect of FTZ against liver aging in aging mice, and its mechanism using ultraperformance liquid chromatography/quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF/MS). Methods: A total of 80 C57BL/6J Narl mice were randomly divided into five groups: 3-month-old group, 9-month-old group, 14-month-old group, 20-month-old group, and FTZ treatment group (20 months old). The mice in the treatment group received a therapeutic dose of oral FTZ extract (1.0 g/kg, on raw material weight basis) once daily during the experiment. The other groups received the corresponding volume of oral normal saline solution. Liver samples of all five groups were collected after 12 weeks, and UPLC-Q-TOF/MS was used to analyze metabolic changes. Orthogonal partial least squares–discriminant analysis (OPLS-DA) was used to analyze the resulting data. Additionally, cholesterol (TC), triglyceride (TG), aspartate aminotransferase (AST), alanine aminotransferase (ALT), secretion levels of TNF-α, IL-6, 5-LOX, and COX-2, as well as their relative mRNA expression in the liver were determined. Results: The levels of TC, TG, AST, and ALT were increased, and liver tissue structure was damaged. The secretion levels of TNF-α, IL-6, 5-LOX, and COX-2, as well as their relative mRNA expression in the liver also increased with aging. FTZ administration reduced the symptoms of liver aging. The OPLS-DA score plot illustrated the effect of FTZ against liver aging, with N-acetyl-leukotriene E4, 20-hydroxy-leukotriene E4, leukotriene E4, and arachidonic acid among the key biomarkers. The pivotal pathways revealed by pathway analysis included arachidonic acid metabolism and biosynthesis of unsaturated fatty acids. The mechanism by which FTZ reduces the symptoms of liver aging in mice might be related to disorders of the abovementioned pathways. Conclusion: A metabolomic approach based on UPLC-Q-TOF/MS and multivariate statistical analysis was successfully applied to investigate the metabolic trajectory of liver aging. FTZ has a protective effect against liver aging, which may be mediated via interference with the metabolism of arachidonic acid, biosynthesis of unsaturated fatty acids, and downregulation of pro-inflammatory factors in the liver in mice in vivo.